UJI AKTIVITAS ANALGETIK EKSTRAK ETANOLIK DAUN KEREHAU (Callicarpa longifolia Lamk.) PADA MENCIT PUTIH - Eka Siswanto Syamsul; Fitriya Andani; Yulistia Budianti Soemarie (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Pain is a sensory and emotional feelings associated with tissue damage. Leaves kerehau recognized by people Dayak and Kutai as postpartum pain medication. Kerehau leaf has long been known by the public because many have efficacy in medicine. This research to determine the analgesic activity of ethanolic extract of leaves kerehau (Callicarpa longifolia Lamk.) on male white mice (Mus musculus). This is experimental research, randomized complete unidirectional pattern. The animals test were divided into 5 groups with each treatment of 5 mice. Group I (Na CMC 0.5% negative control), Group II (ibuprofen as a positive control), group III - V the ethanol extract of leaves kerehau dose of 150 mg , 300 mg and 600 mg/ Kg BW). Inductor pain acetic acid 0.5 % (ip). Observed number of writhing in mice for 1 hour and calculated percent analgesic . The results obtained in this study has efficacy as an analgesic with Strength of power dose I: 51.65 %, dose II: 65.40 %, and dose III: 75.98 %.